Improving the sustainable development of tourism based on the application of the environmental management system - Shcherbakova Nadiia; Tsypko Victoria; Riaboshtan Liudmyla; Lavrynovych Elena; Vasylyshyn Iaroslav (E3S Web of Conferences)
The quality of the environment, both natural and anthropogenic, is of great importance for tourism. The tourism sphere includes many types of activities that can have negative environmental consequences. Many of these impacts are related to the construction of public infrastructure such as roads and airports, as well as tourist facilities including resorts, hotels, restaurants, shops, golf courses and marinas. Methodology is based on scientific and special research methods. Methods are used: analysis, synthesis, systematization, classification, generalization of economic and methodical sources. The study of the features of the sustainable development of tourism based on the application of ecological management necessitated the study of the future of sustainable tourism, because for its development, it is necessary to have, in its practical forms, the reconciliation of antagonistic interests and goals that will affect the partnership and cooperation between decision-makers, operators and consumers, which will contribute to the long-term common interest. The article solves important problems of the tourism sphere through the prism of the analysis of relevant indicators of ecological characteristics for various subjects of the sphere of ecotourism. It is noted that the negative consequences of tourism occur when the level of use of natural resources by tourists exceeds the permissible level of use of the environment. Uncontrolled tourism poses potential threats to many natural areas around the world. It has been proven that rational ecological management of tourist facilities can increase the benefit for natural areas. But this requires careful planning of controlled development based on an analysis of the area's ecological resources.